The Characteristics of Government Sukuk Return Volatility Before and During Covid-19, and After Implementation of Primary Dealer System - Tia Rahmina; Achsani, Noer Azam; Santoso, Moch. Hadi (Jurnal Manajemen & Agribisnis, 2022)
Government Sukuk (SBSN) has been launched since 2008, but it assumed illiquid. Therefore, the Ministry of Finance in 2020 regulates primary dealer for SBSN. At the same time, the restrictions on mobility due to the Covid-19 Pandemic in 2020 triggered negative sentiment. It increased volatility in the capital market. Asymmetric volatility occurs when market crash. The purpose of this study is to identify characteristics of government sukuk return volatility before and during the Covid-19 pandemic and after the implementation primary dealer system using EGARCH. The results show that SBSN responds to shocks more quickly during the pandemic. The benchmark series responds to shocks faster than non-benchmark. Moreover, during the pandemic, PBS04, PBS05, PBS07 and PBS22 were categorized high risk-high return. PBS02, PBS11, PBS14, PBS19, and SR10 were categorized low risk-low return. PBS17, PBS12, PBS15 and PBS21 were catogerized high risk-low return. PBS02, PBS14, PBS19, PBS17, PBS12 and SR10 have negative asymmetric return volatility. Furthermore, SBSN benchmark series PBS05 and PBS25 were categorized high risk-high return, PBS02 were categorized low risk-low return, and PBS026 were categorized high risk-low return. Most of the benchmark series have negative asymmetric return volatility. Keywords: Asymmetric volatility return, Covid-19, EGARCH, government sukuk, primary dealer